Baptista Tafolla, Miquel de Morales i Joan Ximenes. Violència, amistat, criminalitat i amor. Joc de contrastos d'un triangle amorós del darrer terç del segle XVI. - MOMPÓ NAVARRO, JACOB (Scripta, 2020)
For some unknown reason, Baptista Tafolla declared in front of the Inquisition that he had committed the crime of sodomy with other men. In his statements appear the names of Father Miquel de Morales, a Trinitarian religious of Sant Bernat d'Alzira monastery, and Joan Ximenes, the squire of the Lord of Miraflores. The effective inquisitorial procedure converted the accused of a sodomy trial into testimonies in other trials. In this way, the three vertexes of a love triangle converge in a documentation that highlights the moments of violence and criminality that our protagonists experienced, although tthey enjoyed a lasting relationship between friendship, desire and love.